COMPLEXITY AND SIMPLICITY OF THE METAL-SUPERCONDUCTOR-INSULATOR TRANSITION IN THE (TL1-XPBX)SR2(CA1-YYY)CU2O7-DELTA SYSTEM - Liu, R; Edwards, P (1991)
The (Tl1-xPbx)Sr2(Ca1-yYy)Cu2O$-7-$del ta$/ system exhibits the highest superconducting transition temperature, Tc=110 K, at x=0.5 and y=0.2, yet observed in the TlBa2CaCu2O7-δ (1212) structure type. This complex, six-blend combination of metallic elements which make up the material is, however, compensated by a relatively simple crystal structure, which bears many similarities to that of 90 K superconductor YBa2Cu3O7-δ. Here, we report some of the important features of the cation-substitution chemistry of the title compound, drawing attention to fundamental changes in the electronic properties and the Metal-Superconductor-Insulator transition of the (Tl1-xPbx)Sr2(Ca1-yYy)Cu2O$-7-$del ta$/ system as Tl3+ and Ca2+ is replaced by Pb4+ and Y3+, respectively. In addition, we also report preliminary results concerning the effects of the chemical substitution in the (Tl,Pb)O layers.